2015
DOI: 10.3109/13880209.2014.996820
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme (ACE) inhibitory potential of standardizedMucuna pruriensseed extract

Abstract: Context: Mucuna pruriens Linn. (Fabaceae) is a tropical legume, traditionally used for controlling blood pressure. Inhibition of angiotensin-converting enzyme (ACE) is one of the successful strategies for controlling hypertension.Objective: The present study evaluated the ACE inhibition potential of the standardized extract of M. pruriens seeds. Materials and methods: Standardization of the extract and its fractions were carried out by RP-HPLC method [methanol and 1% v/v acetic acid in water (5:95 v/v)] using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 12 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…At the same time, ACE inhibitors may cause hyperkalemia with the cause of aldosterone depletion (Hodsman et al, 1983;Warren & O'Connor, 1980 (Chaudhary, De, Bhadra, & Mukherjee, 2015). At the same time, ACE inhibitors may cause hyperkalemia with the cause of aldosterone depletion (Hodsman et al, 1983;Warren & O'Connor, 1980 (Chaudhary, De, Bhadra, & Mukherjee, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, ACE inhibitors may cause hyperkalemia with the cause of aldosterone depletion (Hodsman et al, 1983;Warren & O'Connor, 1980 (Chaudhary, De, Bhadra, & Mukherjee, 2015). At the same time, ACE inhibitors may cause hyperkalemia with the cause of aldosterone depletion (Hodsman et al, 1983;Warren & O'Connor, 1980 (Chaudhary, De, Bhadra, & Mukherjee, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the inhibitory effect of methanol extract and aqueous fraction of the Mucuna pruriens Linn. (Fabaceae) on ACE activity was investigated, and IC 50values were 52.68 ± 2.02 and 67.65 ± 2.40 mg/mL, respectively(Chaudhary, De, Bhadra, & Mukherjee, 2015). In another study, Peperomia pellucida L., Nasturtium officinale L., and Sesamum indicum L.showed in vitro inhibitory effect on ACE activity.…”
mentioning
confidence: 97%
“…According to the information from TCM databases [27], 5-hydroxy- l -tryptophan is extracted from Mucuna pruriens seed, which has been indicated the function of antiproliferative effect [37], neuroprotective effect [38], control blood pressure [39]. In addition, 5-hydroxy- l -tryptophan is also the precursor to biosynthesis of 5-HT.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-ACE activity of the three extracts were demonstrated by different inhibition potential as shown in (Pitt et al, 2000). Recent studies have shown the emergence of a number of plant-derived extracts with potential to provide lead molecules for the synthesis and development of new anti-hypertensive agents (Chaudhary et al, 2015;Gasparotto et al, 2011).…”
Section: Tested Extracts Of R Stricta M Peregrina and A Fragrantimentioning
confidence: 98%